The influence of pedaling rate on bilateral asymmetry in cycling - Smak,W.; Neptune, R. R.; Hull, M. L. (Journal of Biomechanics, 1999)
The objectives of this study were to (1) determine whether bilateral asymmetry in cycling changed systematically with pedaling rate, (2) determine whether the dominant leg as identified by kicking contributed more to average power over a crank cycle than the other leg, and (3) determine whether the dominant leg asymmetry changed systematically with pedaling rate. To achieve these objectives, data were collected from 11 subjects who pedaled at five different pedaling rates ranging from 60 to 120 rpm at a constant workrate of 260 W. Bilateral pedal dynamometers measured two orthogonal force components in the plane of the bicycle. From these measurements, asymmetry was quantified by three dependent variables, the percent differences in average positive power (%AP), average negative power (%AN), and average crank power (%AC). Differences were taken for two cases — with respect to the leg generating the greater total average for each power quantity at 60 rpm disregarding the measure of dominance, and with respect to the dominant leg as determined by kicking. Simple linear regression analyses were performed on these quantities both for the subject sample and for individual subjects. For the subject sample, only the percent difference in average negative power exhibited a significant linear relationship with pedaling rate; as pedaling rate increased, the asymmetry decreased. Although the kicking dominant leg contributed significantly greater average crank power than the non-dominant leg for the subject sample, the non-dominant leg contributed significantly greater average positive power and average negative power than the dominant leg. However, no significant linear relationships for any of these three quantities with pedaling rate were evident for the subject sample because of high variability in asymmetry among the subjects. For example, significant linear relationships existed between pedaling rates and percent difference in total average power per leg for only four of the 11 subjects and the nature of these relationships was different (e.g. positive versus negative slopes). It was concluded that pedaling asymmetry is highly variable among subjects and that individual subjects may exhibit different systematic changes in asymmetry with pedaling rate depending on the quantity of interest.